Seleksi dan Karakterisasi Bakteri Penghasil Kitinase Penghambat Pertumbuhan Cendawan Patogen Tanaman - Azizah Nurmalinda; Nisa Rachmania Mubarik; Lisdar Sudirman (Jurnal Ilmu Pertanian Indonesia, 2020)
Colletotrichum capsici and Fusarium oxysporum are pathogenic fungi that cause anthracnose disease on chili plants (Capsicum annum L.) which can decrease the productivity of chili. The control of the fungus attack is carried out by biocontrol agent of the fungi utilizing chitinase-producing bacteria. Chitinase is an enzyme capable of destroying the fungal cell wall composed of chitin compounds. The aims of the research were to select and to characterize chitinase producing bacteria as biological control agent of Colletotrichum capsici and Fusarium oxysporum. Several methods were carried out in this research, among others: isolation of chitinase bacteria, characterization of chitinase bacteria, measurement of enzyme activity, bacterial antagonistic with pathogenic fungi, observation of fungal hypha damage, and identification of 16S rRNA. The BAE36 and BAD211 isolates are chitinase bacteria isolated from chili plant rhizosphere. The isolate belongs to the Gram-negative bacteria. The inhibitory properties of BAE36 and BAD211 against F. oxysporum and C. capsici are on a scale of 3 (51-75%). The percentage of inhibitory of BAE36 isolate was 66.1% capable of inhibiting the growth of C. capsici and 55% capable of inhibiting the growth of F. oxysporum. The hyphae of C. capsici fungus on the antagonistic test showed a thick and the surface of the hyphae was wavy while the F. oxysporum hyphae was thin and looks empty. Identification of isolate with 16S rRNA described that 99% of BAE36 and BAD211 isolates were similar to Lysobacter enzymogenes. Precipitation of chitinase enzyme of Lysobacter enzymogenes with 30% ammonium sulphate could increase the enzyme activity. The enzyme precipitation could inhibit the growth of mycelia fungi C. capsici and F. oxysporum. Keywords: chili, chitinolytic, Gram-negative, Lysobacter